How empathic are war veterans? an examination of the psychological impacts of combat exposure (2017)
How empathic are battle-experienced war veterans and demobilized ex-combatants? Individuals who have participated in war-related violence tend to show an increased risk of mental health problems, which makes their readaptation to postconflict civilian life much more difficult. This study is the first systematic attempt to evaluate whether war experiences are potentially related to empathic deficit among veterans. Based on a sample of 624 demobilized ex-guerrillas and ex-paramilitaries from the Colombian armed conflict, we identify 3 clearly distinct empathic profiles, suggesting that, while lack of empathy is not generalized among ex-combatants, there is an important subgroup of veterans who present such a dispositional profile. Identification of this critical subgroup will be crucial to policies aimed at assisting postconflict reintegration efforts.